Collective representation at universities – an area of tension between human resource policies and demands of the workforce - Schmidt, Angelika; Wegscheider, Angela (Momentum Quarterly, 2022)
This paper explores changes in labour relations at public Austrian universities using a multi-level analysis and discusses options for action for the collective interest representation of employees. The results show that university career paths are shaped differently than professional careers in organisations due to the UG 2002, the entrepreneurial acting rectorates as well as normative ideas. Universities have increasingly stratified workforces, which are in addition accompanied low identification with the collective employee representation. The employees’ demands on the collective representation of interests relate above all to ensuring transparently accessible and plannable career models.